Analysis of Various Dimensions of Education in Mughal India: मुगलकालीन भारत में शिक्षा के विभिन्न आयामों का विश्लेषण - Kumar, Yogendra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Comparatively, the Mughal period surpassed the Sultanate era not only in arts but also in the field of education. The Mughal rulers were patrons of education and undertook numerous initiatives for its expansion. However, according to Dr. Srivastava, "The Mughal emperors spent on education primarily to earn religious merit, not for the welfare of the people. The dissemination of education for public benefit was not their objective. Instead, people themselves arranged for their children’s education based on their age and circumstances, and these arrangements were generally satisfactory." Nevertheless, the efforts made by the Mughal rulers for the development of education can be extensively studied in the following manner. Abstract in Hindi Language: तुलनात्मक दृष्टि से मुगल काल अन्य कलाओं के साथ-साथ शिक्षा के क्षेत्र में भी सल्तनत काल से आगे था। मुगलकालीन शासक शिक्षा-प्रेमी थे और शिक्षा के विस्तार के लिए उन्होंने अनेकानेक कार्य भी किये परन्तु डॉ. श्रीवास्तव की मान्यता यह है कि “मुगल सम्राट शिक्षा पर जो कुछ व्यय करते थे, वह धार्मिक यश प्राप्त करने के लिए करते थे। जनता की भलाई के लिए शिक्षा का प्रसार करना उनका उद्देश्य नहीं था। जनता स्वयं अपने बच्चों की आयु और परिस्थिति के अनुसार उनकी शिक्षा का प्रबन्ध करती थी। ये प्रबन्ध सन्तोषजनक थे।” फिर भी मुगलकालीन शासकों ने शिक्षा के विकास के लिए जो प्रयास किये उनका विशद अध्ययन निम्न प्रकार से किया जा सकता है। Keywords: भारत, मुगल साम्राज्य, शिक्षा, सल्तनत काल।